Immunohistochemical expression of E-Cadherin in gastric carcinoma in Erbil city, Kurdistan Region - Ara Azad Mustafa; Jalal Ali Jalal (Advanced Medical Journal)
Background and objectives: Gastric carcinoma is at fourth position incidence-wise and holds a second place for deaths due to cancer. The Cadherins represent an important class of the adhesiveness molecules, which play an essential role in the homotypical cell-cell adhesion and in the complex process of invasion and metastasis. The point of this study is to identify the rate of the E-Cadherin immunoexpression in gastric carcinoma in Erbil locality and investigate its association with the clinico-pathological parameters.